Karakteristik Keuangan dan Audit Delay Bukti Empiris pada Perusahaan Manufaktur di Bursa Efek Indonesia - Kent Jefferson Hartanto; Nida Putri Rahmayanti; Ros Nirwana (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to examine the effect of profitability, solvency, company size, and liquidity on audit delay in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. Audit delay reflects the timeliness of audited financial reporting, which is crucial for decision-making by investors and stakeholders. This research uses a quantitative approach with a causal associative design. The population consists of manufacturing companies listed on the IDX, and the sample was selected using purposive sampling, resulting in 25 companies with 100 observations. The data used are secondary data obtained from annual financial reports, and the analysis method employed is panel data regression using STATA 17.The results show that, simultaneously, profitability, solvency, company size, and liquidity have a significant effect on audit delay. However, partially, only solvency has a significant positive effect on audit delay, while profitability, company size, and liquidity do not have a significant effect. This indicates that companies with higher levels of debt tend to require longer audit processes due to increased audit complexity and financial risk.In conclusion, audit delay is more influenced by the financial risk of the company, particularly solvency, rather than profitability, company size, or liquidity. This study contributes to the literature by providing empirical evidence on factors affecting audit delay and can be used as a reference for companies, auditors, and investors in improving the timeliness of financial reporting.